Grethlein, J. (2013). Experience and Teleology in Ancient Historiography. ‘Futures Past’ from Herodotus to Augustine. Cambridge, Cambridge University Press - Sierra-Martín, César (Revista Archai, 2016)
Reseña: Grethlein, J. (2013). Experience and Teleology in Ancient Historiography. ‘Futures Past’ from Herodotus to Augustine. Cambridge, Cambridge University Press